Laura's star - de Rycker, Piet; Rothkirch, Thilo Graf; Madel, Michael; Lindner, Alexander (Warner Home Video ; distributed in the Philippines by Warner Home Video (Phils.), 2005)
Laura is new to the neighborhood, and more than a little homesick. But then she rescues a fallen star who's homesick too ... and shares a friendship that turns her strange new surroundings into a wonderful new place called home.